Mixed Convection in Viscoelastic Boundary Layer Flow and Heat Transfer over a Stretching Sheet (Advances in Applied Mathematics and Mechanics, 2014)
An investigation is carried out on mixed convection boundary layer flow of an incompressibleand electrically conducting viscoelastic fluid over a linearly stretching surface in which theheat transfer includes the effects of viscous dissipation, elastic deformation,thermal radiation, and non-uniform heat source/sink for two general types ofnon-isothermal boundary conditions. The governing partial differential equations forthe fluid flow and temperature are reduced to a nonlinear system of ordinary differentialequations which are solved analytically using the homotopy analysis method (HAM).Graphical and numerical demonstrations of the convergence of the HAM solutions are provided,and the effects of various parameters on the skin friction coefficient and wall heattransfer are tabulated.  In addition, it is demonstrated that previously reported solutions of thethermal energy equation given in [1] do not converge at the boundary, and therefore,the boundary derivatives reported are not correct.